Anti-TNF therapy in IBD exerts its therapeutic effect through macrophage IL-10 signalling. Issue 6 (10th September 2019) - Koelink, Pim J; Bloemendaal, Felicia M; Li, Bofeng; Westera, Liset; Vogels, Esther W M; van Roest, Manon; Gloudemans, Anouk K; van 't Wout, Angelique B; Korf, Hannelie; Vermeire, Séverine; te Velde, Anje A; Ponsioen, Cyriel Y; et al.
Abstract : Objective: Macrophage interleukin (IL)-10 signalling plays a critical role in the maintenance of a regulatory phenotype that prevents the development of IBD. We have previously found that anti-tumour necrosis factor (TNF) monoclonal antibodies act through Fcγ-receptor (FcγR) signalling to promote repolarisation of proinflammatory intestinal macrophages to a CD206+ regulatory phenotype. The role of IL-10 in anti-TNF-induced macrophage repolarisation has not been examined. Design: We used human peripheral blood monocytes and mouse bone marrow-derived macrophages to study IL-10 production and CD206+ regulatory macrophage differentiation. To determine whether the efficacy of anti-TNF was dependent on IL-10 signalling in vivo and in which cell type, we used the CD4+CD45Rb high T-cell transfer model in combination with several genetic mouse models. Results: Anti-TNF therapy increased macrophage IL-10 production in an FcγR-dependent manner, which caused differentiation of macrophages to a more regulatory CD206+ phenotype in vitro. Pharmacological blockade of IL-10 signalling prevented the induction of these CD206+ regulatory macrophages and diminished the therapeutic efficacy of anti-TNF therapy in the CD4+CD45Rb high T-cell transfer model of IBD. Using cell type-specific IL-10 receptor mutant mice, we found that IL-10 signalling in macrophages but not T cells was critical for the induction of CD206+ regulatory macrophages and therapeutic response to anti-TNF. Conclusion: The therapeutic efficacy of anti-TNF in resolving intestinal inflammation is critically dependent on IL-10 signalling in macrophages.